Short term outcomes following robotic arm-assisted lateral unicompartmental knee arthroplasty - Wignadasan, Warran; Chang, Justin; Fontalis, Andreas; Plastow, Ricci; Haddad, Fares S. (Frontiers in Surgery, 2023)
Introduction Robotic-arm assisted medial unicompartmental knee arthroplasty (RA-UKA) is associated with improved accuracy of implant positioning and excellent early functional outcomes. However, there is paucity of evidence regarding outcomes following RA-UKA for isolated lateral compartment osteoarthritis. The purpose of this study was to assess the short-term clinical and patient reported outcomes of lateral compartment UKA, utilising robotic-arm assistance. Methods This was a retrospective study of prospectively collected data of 21 consecutive patients who underwent lateral RA-UKA. The study included 9 (42.9%) males and 12 (57.1%) females with a mean age of 63.4 ± 9.2 years. The Oxford Knee Score (OKS) was measured pre-operatively and at 1-year post-operatively, while range of motion (ROM) and complications were also recorded. Results There was significant improvement of OKS at 1 year's follow up compared with the baseline score (21.8 ± 5.6 vs. 45.2 ± 2.8 respectively; p < 0.001). There was also an improvement in pre-operative ROM when compared to ROM at 1 year's follow up (123.5° ± 8° vs. 131.5° ± 6.3° respectively; p < 0.001). None of the study patients underwent revision surgery within 1 year's follow-up. Conclusion In our study, lateral RA-UKA resulted in significant improvements in clinical and patient reported outcomes with low complications rates. Further long-term comparative studies are needed to assess the utility of lateral RA-UKA vs. conventional UKA.